HUBUNGAN PERILAKU KOMUNIKASI DENGAN KAPASITAS PENYULUH DALAM KEGIATAN PENYULUHAN PERTANIAN DI KOTA KENDARI - Harmoko Harmoko; Iskandar Zainuddin Rela; Salahuddin Salahuddin; Tjandra Buana (Universitas Halu Oleo, 2023)
This research aims to determine the relationship between communication behaviour and the capacity of extension agents in agricultural extension activities in Kendari City. The research location was chosen based on several considerations, such as: being an area with a lower level of change in people's behaviour in communicating with each other, being an area where the majority of people use information technology so that face-to-face communication between people is decreasing. The number of samples in this study was 58 agricultural extension workers because the total population in the study did not reach 100 people, so the number of pieces was taken using a census technique. The method used in this study is a quantitative method using data analysis, namely descriptive analysis and correlation analysis (rank spearman), with the help of SPSS software. The results of this study indicate that communication behaviour, both in terms of knowledge, skills, and intensity, is in the high category, with an average value of 4.27. The capacity of extension agents, which includes the ability to facilitate, access information, technology, and resources, and improve the organization, is also in the high category with an average value of 4.07. The relationship between communication behaviour and extension capacity in Kendari City's agricultural activities is very close, with a correlation coefficient of 0.81 (positive). Extension workers' communication behaviour and ability need to be maintained so that farmers get satisfying new information and knowledge while participating in extension activities.